Pengaruh Pemberian Mozart Classical Music Terhadap Tingkat Kecemasan Pada Ibu Bersalin Kala I Di Praktek Mandiri Bidan Netti Sumarni Kota Padang. - Ulya, Rahmatul; Panduragan, Santhna Letchmi; Fitriana, Shentya (Alifah Health Science Symposium Proceeding, 2024)
Pregnancy involves various physiological changes, including physical changes, changes in the digestive system, respiratory system, urinary tract system, musculoskeletal system, and circulation. During the adaptation process, it is not uncommon for mothers to experience discomfort, one of which is back pain. Although back pain is a physiological issue, it still requires some form of management, such as prenatal yoga.The purpose of this research is to determine the effect of prenatal yoga in reducing back pain in pregnant women in their third trimester in the working area of the Nanggalo Health Center, Padang. A quasi-experimental study design using a pre and post-test design with a control group. The sample in this study consisted of 38 respondents using purposive sampling technique. Data analysis was conducted using the Independent T-Test, which was preceded by tests for normality and homogeneity. Research results: There is an effect of prenatal yoga in reducing back pain in pregnant women in their third trimester. There is an effect of prenatal yoga in reducing back pain in pregnant women in their third trimester in the working area of the Nanggalo Health Center, Padang, with a p-value (0.000<0.050).